PROMOSI DAN SUMBER DAYA MANUSIA TERHADAP KEPUASAN KONSUMEN DAMPAKNYA PADA LOYALITAS KONSUMEN DI TOKO SOES MERDEKA - Dina Febe Kristanti; Wasito Wasito (Jurnal Riset Bisnis dan Manajemen, 2018)
This study aims to determine how much influence of promotion and human resources (HR) at SoesMerdeka store towards consumer loyalty through the satisfaction of the customer as an intervening variable either partially or simultaneously. The research method used is descriptive and verification method with the number of samples counted to 98 respondents. Data collection techniques used were observation and distribution of questionnaires, and analysis methods used are path analysis, multiple correlation, and coefficient of determination. The result shows that promotion, human resource, consumer satisfaction, and consumer loyalty are in enough category. The results of verification research shows promotion and human resources to consumer satisfaction has an influence of 55%, promotion, human resources, and consumer satisfaction on consumer loyalty has an influence of 43.3%.